PRZEGLĄD PIŚMIENNICTWA - Żak, Maciej (Wydział Prawa i Administracji UAM, 1999)
Exchange-Rate Policies for Emerging Market Economies, red. R. J. Sweeney, C. S. Wihlborg, T. D. Willett, Westview Press, A Member of the Perseus Books Group, Boulder 1999, ISBN 0-8133-3019-X, ss. 391.